2020
DOI: 10.3390/antiox9090877
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylaspartylglutamate (NAAG) Pretreatment Reduces Hypoxic-Ischemic Brain Damage and Oxidative Stress in Neonatal Rats

Abstract: N-acetylaspartylglutamate (NAAG), the most abundant peptide transmitter in the mammalian nervous system, activates mGluR3 at presynaptic sites, inhibiting the release of glutamate, and acts on mGluR3 on astrocytes, stimulating the release of neuroprotective growth factors (TGF-β). NAAG can also affect N-methyl-d-aspartate (NMDA) receptors in both synaptic and extrasynaptic regions. NAAG reduces neurodegeneration in a neonatal rat model of hypoxia-ischemia (HI), although the exact mechanism is not fully recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 73 publications
4
14
0
Order By: Relevance
“…Our previous experiments confirmed these observations, showing that application of LY379268 or NAAG not only shortly after HI but also up to 24 h before HI attenuated neurodegeneration [13,28,29]. Our results concerning the prolonged effects of pretreatment with LY379268 are in agreement with those presented by Bond et al [23].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our previous experiments confirmed these observations, showing that application of LY379268 or NAAG not only shortly after HI but also up to 24 h before HI attenuated neurodegeneration [13,28,29]. Our results concerning the prolonged effects of pretreatment with LY379268 are in agreement with those presented by Bond et al [23].…”
Section: Discussionsupporting
confidence: 93%
“…Our results concerning the prolonged effects of pretreatment with LY379268 are in agreement with those presented by Bond et al [23]. The neuroprotective effect of NAAG applied 1 h before hypoxic exposure but after unilateral common carotid occlusion in a neonatal rat model of hypoxia-ischemia was described by Cai et al [27]; however, the neuroprotective effect of NAAG applied 24 h before HI was presented for the first time in our laboratory [29]. Moreover, we showed that the neuroprotective effect of NAAG applied 1 h before HI results from a Figure 3: The effect of LY379268 or NAAG application 24 h or 1 h before HI on caspase-9 (a) and caspase-3 (b) activity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations